Green synthesized Polyscias fulva silver nanoparticles ameliorate uterine fibroids in female Wistar Albino rats - Kenedy Kiyimba; Ayaz Ahmed; Muhammad Iqbal Choudhary; Khadija Rehman; Syed Mehmood Hasan; Abdul Jabbar; Samuel Baker Obakiro; Muhammad Raza Shah; Were Lincoln Munyendo; Eric M. Guantai; Yahaya Gavamukulya (PLoS ONE, 2025)
Uterine fibroids affect a substantial proportion of women in their reproductive age. Despite their effectiveness, surgical options such as hysterectomy are invasive, costly, and associated with recurrences. Pharmacological treatments are non-curative, only alleviate symptoms, and associated with adverse effects. Polyscias fulva (Araliaceae) is traditionally used to manage uterine fibroids in East Africa. In this study we synthesized Polyscias fulva silver nanoparticles (PFAgNPs), evaluated their toxicity and activity against monosodium glutamate (MSG)-induced uterine fibroids in Wistar albino rats. The UV-visible spectroscopy showed maximal absorbance at 425 nm with adequate stability at varying temperatures, pH and storage conditions. Dynamic light scattering (DLS) analysis revealed an average hydrodynamic size of 107.4 d.nm, polydispersity index of 0.264, and zeta potential of -18.3 mV. X-ray diffraction (XRD) confirmed the crystalline nature of PFAgNPs with an average size of 25 nm while scanning electron microscopy (SEM) showed a spherical shape with an average size of 35 nm. The PFAgNPs caused lethargy, hyperventilation, and hyperactivity at a dose of 300 mg/kg BW, whereas 2000 mg/kg caused severe toxicity, resulting in death in acute toxicity testing. The no observed adverse effect level was 50 mg/kgBW, the lowest observed adverse effect level was 100 mg/kgBW, and median lethal dose (LD50) was 1000 mg/kg. The PFAgNPs significantly decreased (P < 0.05) serum proteins, cholesterol, estrogen and progesterone alongside preservation of the histoarchitecture of the uterus. Further research is needed to investigate the clinical safety of PFAgNPs in managing uterine fibroids.